Clinical and microbiological profile of diabetic foot ulcers in a tertiary care setup: a cross sectional analysis - Rai, Siddharth; Uppal, Harleen; Sharma, Arvind Kumar; Gupta, Anil Kumar (International Journal of Advances in Medicine, 2021)
Background: Diabetes associated neuropathy and vasculopathy leads to development of diabetic foot ulcers (DFU). They are responsible for considerable morbidity and a significant cost of health‐care worldwide. The magnitude of the problem becomes worse in regions where foot care is inadequate like in our country. The aim of the study to determine the microbiological profile and antimicrobial susceptibility pattern of organisms isolated from patients with diabetic foot ulcers. Methods: The study was a cross sectional study done at King George’s Medical College, Lucknow from 2012-2014 in Lucknow, Uttar Pradesh. Based on the inclusion criteria sample were collected from 112 patients. The standard protocol for the identification of microorganisms was followed. A descriptive analysis of the data was done. Results: Out of the 112 ulcers total 180 isolates were found. Of the 112 cases, 78 were monomicrobial, 32 were polymicrobial, and 2 cases were sterile on culture. The most common bacteria found was Staphylococcus aureus. Most of the staphylococcus isolated were sensitive to vancomycin, teicoplanin, cephalosporins, linezolid levofloxacin and pipercillin-tazobactum. Nearly 65% of S. aureus were methicillin‐resistant S. aureus. Conclusions: This study compiled clinical and microbiological profile of diabetic foot ulcers along with their antibiotic susceptibility patterns. Our study illuminates light on a high figure of neglected and poorly treated NHUs which could have been managed well and early treatment will prevent devastating consequences such as sepsis and amputation.